HERPETOFAUNAL REMAINS (ANURA, CROCODYLIA, TESTUDINES, SQUAMATA) FROM THE LATE MIOCENE OF THE CREVILLENTE AREA (SE SPAIN): PALAEOBIOGEOGRAPHICAL AND PALAEOECOLOGICAL IMPLICATIONS - Rafael Marquina Blasco; DAVID MORALES-FLORES; ÁNGEL D. BARTOLOMÉ-BOMBÍN; PLINIO MONTOYA (Rivista Italiana di Paleontologia e Stratigrafia)
In the present work we describe the palaeoherpetofaunal remains from the Crevillente 2 (MN11) and Crevillente 15 (MN12) sites (Crevillente, Alicante, Spain), which is a key area for understanding the faunal turnovers during the Late Miocene. Crevillente 2 has yielded a diverse assemblage composed of anurans (Pelophylax sp.), crocodylians (Crocodylia indet.), lizards (cf. Scinciformata indet. 1 and 2, cf. Timon sp., Lacertidae indet. 1 and 2, Ophisaurus s.l. sp., and Pseudopus sp.) and ophidians (Colubridae indet. 1 and 2, Neonatrix sp., and Viperidae indet. Oriental morphotype). The probable presence of Timon is discussed; if confirmed, it would be the oldest occurrence of the genus. The faunal composition is consistent with that from other coeval Iberian sites. The assemblage includes European autochthonous taxa (Lacertidae and Ophisaurus s.l. sp.) and taxa that likely arrived from Asia or North America during the Oligocene-Miocene transition or the Early Miocene, such as Pseudopus, Oriental vipers and, probably, Neonatrix. The studied assemblage in Crevillente 15 is limited to turtles (Paleotestudo sp. and Testudines indet.) and crocodylians (Crocodylia indet.). At both localities, the surrounding landscape must have been dominated by open habitats with patches of forest/shrubland formations close to water bodies. The application of the Herpetological Ecophysiological Groups method to Crevillente 2 indicates that the mean annual rainfall must have been higher than currently recorded in the area. the Herpetological Ecophysiological Groups method to Crevillente 2 indicates that the mean annual rainfall must have been higher than that currently recorded in the area. Our results indicate that the Iberian palaeoherpetofauna of those chronologies were few barely affected by the Vallesian Crisis.